2009
DOI: 10.1002/cncr.24370
|View full text |Cite
|
Sign up to set email alerts
|

Synovial sarcoma

Abstract: BACKGROUND: The optimal treatment for synovial sarcoma remains controversial. Treatment, outcome, and prognostic factors in patients treated in a single institution were examined. METHODS: Synovial sarcoma patients who underwent surgery at the Rizzoli Institute between 1976 and 2006 were identified and analyzed. RESULTS: Characteristics of the 250 patients (128 female; 122 male) included: median age, 37 years (range, 7‐83 years); 177 (71%) with tumors in the lower extremity, 40 (16%) with tumors in the upper e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
73
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(79 citation statements)
references
References 30 publications
3
73
1
Order By: Relevance
“…This rate seems to be lower than in other studies reported before. It has to be mentioned that in these trials median follow-up was longer (from 5.5 up to 13.2 years) as compared to our study (23 months) [9,10,16,17,24]. …”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…This rate seems to be lower than in other studies reported before. It has to be mentioned that in these trials median follow-up was longer (from 5.5 up to 13.2 years) as compared to our study (23 months) [9,10,16,17,24]. …”
Section: Discussionmentioning
confidence: 74%
“…Other studies reported a higher DFS rate after 5 years, i.e. between 58 and 62% mainly due to the inclusion of more patients, as well as a longer median follow-up [9,17,24,29]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Location is mainly 71% in the lower and 16% in the upper extremities (Palmerini et al, 2009). Local symptoms in specific sites can also be observed.…”
Section: Clinical Featuresmentioning
confidence: 97%
“…It usually affects the extremities of young patients around the age of 35 years [1, 3]. Although called synovial sarcoma, it is rarely intra-articular [4].…”
Section: Introductionmentioning
confidence: 99%